Highly Efficient Oligonucleotide Transfer into Intact Yeast Cells Using Square-Wave Pulse Electroporation. (August 1998) - Barre, François-Xavier; Mir, Lluis M.; Lécluse, Yann; Harel-Bellan, Annick
Here, we present a rapid and reproducible procedure based on square-wave pulse electroporation that allows efficient penetration of synthetic oligonucleotides into intact yeast cells. This procedure was successfully used to modify the yeast genome with small amounts of oligonucleotide.